Revision of the genus Macrostomus Wiedemann (Diptera, Empididae, Empidinae). III. The limbipennis species-group - Rafael, José Albertino; Cumming, Jeffrey M. (Zootaxa, 2012)
All species of Macrostomus Wiedemann allied with Macrostomus limbipennis (Bezzi), are treated in the limbipennis species-group, which is defined on the basis of characters of the male and female terminalia, and a relatively wide female frons. Threecurrently recognized species and two new species are included, namely M. inflatus, sp. nov. from Brazil (Federal District), M.limbipennis (Bezzi, 1909), M. nigriventris (Macquart, 1846), M. nitidus, sp. nov. from Brazil (Goiás and Mato Grosso states)and M. penai Rafael & Cumming, 2006. All primary types were examined and a lectotype is designated for M. limbipennis(Bezzi, 1909). A key to the species is presented along with the geographical distribution pattern exhibited by the limbipennis species-group.